A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel; Ivanova, Maria S. (Zootaxa, 2018)
The Cyana bianca (Walker, 1856) species-group is revised. Cyana bianca malayana Bucsek, 2012 is upgraded to the species level. A new species, C. indosinica Volynkin & Černý, sp. nov. (China: Yunnan, Thailand, Laos, Vietnam) and a new subspecies, C. quadripartita vieta Volynkin & Černý, ssp. nov. (Vietnam) are described.